Development of "Game of Contract" for Interactive edutainment / Sylvia Gala Mong ... [et.al.] - Mong, Sylvia Gala; Awang Yunus, Awang Ihsan; Wan Muhammad, Wan Mohd Nurdden; Saaid, Mohd Nabil Fikri; Abdul Hadi, Nurulhudaya (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Parties in the construction industry legal relationship are officiated through construction contracts comprising principles and elements of contracting parties' obligations and management process. The contract is rather legaloriented, which is sometimes tricky to understand. Most of the students are struggling with the Professional Practice subject. Based on the preliminary survey, students encountered issues in understanding the conditions of the contract, and its standard clauses (81 clauses) are getting more complex and challenging. It leads to the dry subject syndrome. Games of Contract (GoC) is developed in gaining students' interest in understanding construction contracts in a leisure-learning environment through gamification. GoC is a board game that provides a platform to offer the students an overview of the construction contract. GoC provides the information on the process of post-contract stages, from the site possession until the preparation of the final certificate. The board game is administered by answering questions related to the clauses in the contract.